On the Convergence of Iterative Processes for Generalized Strongly Asymptotically 𝜙-Pseudocontractive Mappings in Banach Spaces - Vittorio Colao (Journal of Applied Mathematics)
We prove the equivalence and the strong convergence of iterative processes involving generalized strongly asymptotically 𝜙-pseudocontractive mappings in uniformly smooth Banach spaces.